The Mediating Role of Brand Image on Product Quality, Price, and Location Toward Millennial Cluster Property Purchase Decisions in Bogor Regency - Efson Sairi; Agus Setyo Pranowo; Hari Muharam (PT. Maju Malaqbi Makkarana, 2026)
The increasing development of cluster property in Bogor Regency has intensified competition among developers, particularly in attracting millennial consumers who are more critical, rational, and digitally informed in making housing purchase decisions. This study aims to analyze the mediating role of brand image in the influence of product quality, price, and location on millennial cluster property purchase decisions in Bogor Regency. A quantitative approach was employed using a descriptive and verificative research design. Data were collected through questionnaires distributed to 220 millennial consumers who had experience purchasing or were directly involved in purchasing cluster property in Bogor Regency. The research instrument was measured using a five-point Likert scale and analyzed using structural equation modeling to test direct and indirect effects. The results show that product quality, price, and location have positive and significant effects on brand image. Product quality, price, location, and brand image also have positive and significant effects on purchase decision. Furthermore, brand image partially mediates the effects of product quality, price, and location on purchase decision. These findings indicate that millennial property purchase decisions are shaped by both rational property attributes and psychological trust in developer reputation.